Evaluación de la Opacidad Generada por los Buses a diésel en el Terminal Terrestre del Cantón Pujilí de la Provincia de Cotopaxi en el periodo 2018 – 2019. - Chasipanta Vega, Sonia Maribel (2019)
The purpose of this research was to evaluate the opacity generated by diesel buses in the Terrestrial terminal of Canton Pujilí, the research was planned in four objectives, determine the number of diesel buses to be evaluated, evaluate the opacity of buses using the AVL DITEST 1000 with its accessory opacimeter DISMOKE 480, compare with the NTE INEN 2207: 2002 regulations, propose proposals for mitigation and environmental control. Through an on-site visit it was determined that there were three cooperatives with a total of 70 units, for the evaluation of the buses the measurement protocol established by the NTE INEN 2202: 2000 standard was used with the free acceleration method that indicates the steps and Vehicle data required by the Team for evaluation. The data obtained from the registration of each bus indicates that all buses evaluated are from 2000 and higher until 2016, taking into account that these means of transport have a useful life of 20 years according to what ANT establishes ( National Transit Agency), the data obtained from the opacity of each bus were compared according to the permissible limits established by the NTE INEN 2207: 2002 Standard, where 15 of the buses do not comply with the regulations, the buses with the percentage of opacity plus High are the number 05 of the Vivero cooperative with an opacity percentage of 73.3% and the unit 15 of the cooperative October 14 with an opacity percentage of 74.9% exceeding the permissible limits according to the Regulations, while 35 buses comply with the permissible limits according to the regulations, knowing that the maximum requirements for mobile diesel sources are: from the year 2000 onwards it is 50% opacity. With the results and information obtained, the proposals for Environmental Mitigation and Control were made to reduce air pollution by mobile diesel sources in the Canton and therefore in the Province.